2012
DOI: 10.1007/s00441-012-1396-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific processing and release of the hormone-like precursor and candidate tumor suppressor gene product, Ecrg4

Abstract: The human open reading frame C2orf40 encodes esophageal cancer related gene-4 (Ecrg4), a newly recognized neuropeptide-like precursor protein whose gene expression by cells in vitro, over-expression in mice in vivo and knock-down in zebrafish affects cell proliferation, migration and senescence, progenitor cell survival and differentiation and inflammatory function. Unlike traditionally secreted neuropeptide precursors however, we find that Ecrg4 localizes to the epithelial cell surface and remains tethered af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…20 Moreover, further processing of this 148-amino acid molecule into smaller peptides is reportedly required for its inhibitory function 24 and smaller processed peptides are found in cell culture medium. 25,26 Thus, C2ORF40 is not only a prognostic biomarker and potential therapy target in breast cancer; C2ORF40 gene product or C2ORF40-derived peptide might potentially be a suitable biotherapeutic reagent for breast and other types of tumors. Restoring C2ORF40 expression in tumors, either by epigenetic therapy or application of recombinant C2ORF40-derived peptide, may represent a promising therapeutic approach for breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, further processing of this 148-amino acid molecule into smaller peptides is reportedly required for its inhibitory function 24 and smaller processed peptides are found in cell culture medium. 25,26 Thus, C2ORF40 is not only a prognostic biomarker and potential therapy target in breast cancer; C2ORF40 gene product or C2ORF40-derived peptide might potentially be a suitable biotherapeutic reagent for breast and other types of tumors. Restoring C2ORF40 expression in tumors, either by epigenetic therapy or application of recombinant C2ORF40-derived peptide, may represent a promising therapeutic approach for breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] It was demonstrated that Ecrg4 was first produced as a precursor protein of 148 amino acids, and then was proteolytically processed into several different fragments. [10][11][12][13] Therefore, the cleaved Ecrg4 fragment(s) seems likely to transmit growth retardation signals into the cells in an autocrine/paracrine manner, rather than Ecrg4 directly inhibits cell proliferation machinery in the cells.…”
Section: Introductionmentioning
confidence: 99%
“…An additional study also demonstrated that C2ORF40 causes cell cycle G1 phase block via interaction with Transmembrane Protease, Serine 11A in ESCC (27). Previous studies have indicated that C2ORF40 may be processed and released from the cell surface to function biologically (35,36). However, a detailed molecular mechanism for the tumor suppressing function of C2ORF40 protein remains to be clarified in ESCC.…”
Section: Discussionmentioning
confidence: 96%